Penerapan Metode GASING (Gampang, Asyik, Menyenangkan) pada Penjumlahan Bilangan Bulat Positif untuk Meningkatkan Hasil Belajar Siswa dan Karakter Daya Juang (Mujahadah) Siswa Kelas VII G: Madrasah Tsanawiyah Negeri 2 Mojokerto, Jawa Timur, Indonesia - Zaimah, Husnuz (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2025)
This research aims to improve student learning outcomes and fighting spirit character (mujahadah) in positive integer addition material through the implementation of the GASING method (Easy, Fun, Enjoyable). The research subjects were students of class VII G at MTsN 2 Mojokerto. The research method used was qualitative with a case study approach. Data collection was conducted through participant observation, in-depth interviews, and documentation during the learning process. The research findings show that the implementation of the GASING method can improve student learning outcomes through three main stages: concrete, abstract, and mental calculation. Students showed significant changes in their perception of mathematics from a frightening subject to an enjoyable one. Student learning activities increased in aspects of participation, enthusiasm, and concept understanding. The learning atmosphere became more enjoyable and facilitated students in understanding positive integer addition concepts. Students' fighting spirit character also showed development during the learning process, manifested in perseverance, never-give-up attitude, internal motivation, and increased self-confidence. Based on the research results, it can be concluded that the GASING method is effective in improving learning outcomes and students' fighting spirit character in positive integer addition material at class VII G MTsN 2 Mojokerto. The method successfully transforms students' perception of mathematics and creates optimal learning dynamics through a combination of teaching aids, enjoyable learning atmosphere, and gradual approach. Keywords: GASING method, positive integer addition, learning outcomes, students' fighting spirit